A learning process towards person‐centred care: A second‐year follow‐up of guideline implementation. (19th March 2021) - Kindblom, Kristina; Edvardsson, David; Boström, Anne‐Marie; Vikström, Sofia
Abstract: Background: Research claims that 'learning by doing' creates new thinking, often leading to new practice. Objectives: The aim was to explore and describe the staff learning process from the first to the second year when adopting person‐centred care into clinical practice in a nursing home for persons with dementia. Method: The data consisted of poster texts from staff and written notes by researchers obtained from the group discussions. The study involved 24 care units (200 staff). Content analysis was chosen as method to explore the learning process. Result: The staff described the actions that they took during year 1 and year 2, in which five categories emerged, activities, environment, information, priorities and staff routines. With researchers' analysis the categories together created the learning process and formed a sub‐theme. They further formed an overarching theme from simplicity to complexity and consensus. Staff changes year 1 pertained more to planning and doing, while year 2 changes constituted a larger complexity of person‐centred care with reflection, collaborative learning and a mind‐set change. Conclusion: Staff chose the development area, and the learning process was illuminated by the researchers. This underscores the value to visualise and verbalise the steps of change as well as include these steps in the design of an implementation process. The concept of person‐centred care could be viewed on different levels. The findings may contribute to a more comprehensive understanding of staff learning process when implementation of person‐centred care. Implications for practice: Making staff's learning process visible can be a guide for improvement and change from a generic care towards person‐centred care. The Regional Board of Research Ethics approved the study (Reg no. 2010/1234‐31/5).